Predictors of purchase intention of luxury South Sea pearls - 't Hart, B.; Teah, Min; Butcher, Luke (Elsevier, 2016)
This study aims to gain further insight into the reasons behind the decline in sales of luxury South Sea pearls by exploring the different antecedents of consumers’ purchase intention using the theory of planned behaviour. Data were collected using a self-administered questionnaire and analysed using a combination of statistical analysis techniques. Findings showed that attitudes, novelty seeking and self-efficacy are significant predictors of purchase intention, while interpersonal influences are not a significant predictor. This study provides industry practitioners, researchers, policy makers and retailers with new insights into the pearling industry so they are able to better develop products, design branding strategies and form policies which address current consumer behaviour.